The inventory of callous–unemotional traits: psychometric properties among referred and non-referred portuguese female juveniles - Pechorro, Pedro (2017)
The presence of callous-unemotional (CU) traits delineates a subgroup of male youth with severe conduct disorder and antisocial behavior, but little research has been done among female youth. Drawing on 377 female adolescents (103 selected from forensic settings and 274 selected from school settings) from Portugal, the current study is the first to simultaneously examine the psychometric properties of the Inventory of Callous Unemotional Traits (ICU) in incarcerated female youth and community youth. The results support the use of the ICU in terms of its factor structure, and internal consistency despite the fact an item had to be removed from the Callousness dimension. Statistically significant positive associations were found with measures of psychopathic traits and aggression, as well as non-significant associations with empathy and social anxiety. Significant associations were also found with several indicators of delinquent careers including age of criminal onset, age of first contact with the law, Conduct Disorder symptoms and diagnosis, crime seriousness, previous violent offending, number of criminal charges, alcohol use, and drug use. Findings are discussed in terms of the use of the ICU among female juvenile offenders and community youths.